Long‐term effectiveness of intralesional triamcinolone acetonide therapy in orofacial granulomatosis: an observational cohort study. (April 2014) - Fedele, S.; Fung, P.P.L.; Bamashmous, N.; Petrie, A.; Porter, S.
<x xml:space="preserve">Abstract</x> What's already known about this topic? It has been suggested that intralesional corticosteroid therapy is effective in controlling the permanent disfiguring swelling of orofacial granulomatosis (OFG); however, robust supporting evidence is lacking due to the variable and inconsistent design of available studies. What does this study add? This is the first cohort study on intralesional therapy to employ robust cohort design, consistent methodology and a standardized regimen of triamcinolone injections. It provides reliable evidence of long‐term effectiveness in reducing the orofacial swelling of OFG.